Peningkatan Kualitas Pendidikan Sekolah Dasar Islam Amanah Kekait Melalui Kemah Bakti Masyarakat Mahasiswa - Mohammad Archi Maulyda; Muhammad Tahir; Arif Widodo; Deni Sutisna; Radiusman Radiusman; Muhammad Syazali; Muhammad Sobri (Institut Agama Islam Negeri Bengkulu, 2020)
Community Service Camp (KBM) is a PGSD student activity as a form of implementation of one of the Higher Education Tri Dharma values namely Community Service. This activity is a routine activity that is carried out once a year. For the 2020 period, KBM activities will be carried out in Batu Butir Village, Kekait District, North Lombok Regency. This activity lasted for 1 month starting on January 2 to February 2, 2020. One of the sub-units of this activity was an effort to improve the quality of education in SDI